A study of a low pressure ratio vapor injection scroll compressor for electric vehicles under low ambient conditions. (November 2021) - Zhang, Xinxin; Su, Lin; Li, Kang
Highlights: A lower pressure ratio vapor injection scroll compressor is devised and tested. Performance of the injection compressor is studied under low ambient temperatures. The injection process is more efficient at lower evaporation temperatures. A theory model with correlations of compressor efficiencies is built and verified. Abstract: Vapor injection technology is a promising method to improve the performance of heat pump systems on electric vehicles. In this work, an experimental study on a low pressure ratio vapor injection scroll compressor was carried out under low ambient temperature conditions. Comparative experiments were conducted for various injection pressures, compressor speeds, and evaporation temperatures. The typical flow and heat transfer characteristics were obtained and analyzed, especially the compressor volumetric efficiency and compressor efficiency. The results showed that the heating performance was improved and discharge temperature was reduced with the increasing injection pressure at a higher compressor speed and a lower evaporation temperature. The volumetric efficiency and compressor efficiency both decreased with the increasing injection pressure. The maximum heating capacity could increase by 16% and the maximum discharge temperature reduction would reach 8 °C for the vapor injection process compared with non-injection process under the evaporation temperature of -22 °C. Furthermore, a semi-empirical model with correlations of volumetric efficiency and compressor efficiency was developed. The results were validated and showed a reasonable agreement with experimental results.